Honest on mondays: Honesty and the temporal distance between decisions and payoffs - Bradley J. Ruffle; Yossi Tobol (Institute for the Study of Labor (IZA), 2013)
We show that temporally distancing the decision task from the payment of the reward increases honest behavior. Each of 427 Israeli soldiers fulfilling their mandatory military service rolled a six-sided die in private and reported the outcome to the unit's cadet coordinator. For every point reported, the soldier received an additional half-hour early release from the army base on Thursday afternoon. Soldiers who participated on Sunday (the first work day of the week) are significantly more honest than those who participated later in the week. We derive practical implications for eliciting honesty.
Keywords: C93; D63; 330; experimental economics; honesty; temporal distance; soldiers